Annellated 1,3,4,2-Triazaphospholenes-Simple Modular Synthesis and a First Exploration of Ligand Properties - Ferdinand Richter; Nicholas Birchall; Christoph M. Feil; Martin Nieger; Dietrich Gudat (Molecules, 2022)
The successful use of 1,3,4,2-triazaphospholenes (TAPs) as organo-catalysts stresses the need for efficient synthetic routes to these molecules. In this study, we establish the [1 + 4]-cycloaddition of PBr3 to azo-pyridines as a new approach to preparing pyrido-annellated TAPs in a single step from easily available precursors. The modular assembly of the azo-component via condensation of primary amines and nitroso compounds along with the feasibility of post-functionalization at the P–Br bond under conservation of the heterocyclic structure allows, in principle, to address a wide range of target molecules, which is illustrated by prototypical examples. The successful synthesis of a transition metal complex confirms for the first time the ability of a TAP to act as a P-donor ligand. Crystallographic studies suggest that hyperconjugation effects and intermolecular interactions induce a qualitatively similar ionic polarization of the P–Br bonds in TAPs as in better known isoelectronic diazaphospholenes.